Wizerunek stereotypowego Hiszpana w społeczeństwie polskim i hiszpańskim - Wełna, Aleksandra (Investigationes Linguisticae, 2011)
The article deals with the subject matter of stereotypical image of Spaniard in Polish and Spanish tradition. The question of stereotyping, which, amongst other aspects, carries the knowledge of the world and mentality that is necessary in order to fully understand the culture of a given nation, has been dealt with by me in relation to the multiculturalism. What is the stereotypical image of Spaniard? Is our positive or negative attitude towards them reflected in the terminology we use to describe the Spanish? I have tried to answer these, and other, questions based on the survey carried out amongst Polish and Spanish students.